Sustainability assessment of Cerrado and Caatinga biomes in Brazil: A proposal for collaborative index construction in the context of the 2030 Agenda and the Water-Energy-Food Nexus - Arcoverde, Gustavo Felipe Balué; Menezes, Julia Alves; Paz, Mariana Gutierres Arteiro; Barros, Jocilene Dantas; Guidolini, Janaína Ferreira; Branco, Evandro Albiach; De Andrade, Pedro Ribeiro; Pulice, Sergio Mantovani Paiva; Ometto, Jean Pierre Henry Balbaud (Frontiers in Physics, 2023)
2030 Agenda framework represents an opportunity for the co-development of local indicators and share the same principles of cross-sectoral of the Water-Enery-Food Nexus. The aim of this research was to develop a quantitative-collaborative methodology for constructing indicators and indexes for the sustainability of Cerrado and Caatinga Brazilian biomes considering the connection and synergies between Nexus perspective and the 2030 Agenda's SDG-Targets framework. The study was applied in 2,512 municipalities that make up the total of mentioned biomes. The methodology consists of four major blocks: (i) identification and construction of indicators based on the association of them with one or more 2030 Agenda's Targets, in a collaborative way from expert groups; (ii) generation of weights by indicator considering: leverage, according to the number of Targets assignments, and; importance, attributed by experts for each indicator to the Target; (iii) generation of SDG Indexes, considering the performance of the SDGs; Nexus Performance, considering different weights between the SDGs; Nexus Synergistic, the standard deviation between the SDGs; and Nexus Overall, a combination of the last two and; (iv) sensitivity analysis for performance indexes considering the assignment of zero values to the governance indicators. In general, the regions of MATOPIBA, northern and western of Cerrado and the Caatinga, were on average the areas of greatest vulnerability. The meaning of the Targets that respond to this inequality are related to eradicating hunger, sustainable and climate resilient production systems, universal affordability to water, water quality, efficiency of multiple water uses, affordability to energy and the participation of renewable energies. It was found that in the areas of better performance, there is also greater inequality in the dimensions of the Nexus and therefore many of these areas were penalized, smoothing the inequalities in the Nexus Overall Index. The states and areas with the worst Nexus dimensions performances and with insufficient governance measures were: North and northwest of Bahia and municipalities bordering the State of Tocantins – Food; Maranhão and Piauí, northeast of Mato Grosso, northwest of Goiás, Rio Grande do Norte and Paraíba - Water, and; Maranhão, extreme southeast of Pará and more sparsely in Paraíba – Energy